Infectious Diseases, Stock Market Volatility, and Public Opinion on Home Buying in the United States: Implications from COVID-19 and Beyond - Christopher Olds (Advances in Social Sciences Research Journal, 2020)
The study evaluates whether there are limits to an excess in consumptive behaviors during periods where infectious disease outbreaks produce unpredictable changes in equity markets. While there is evidence of panic buying in these periods such that people increasingly acquire goods that they do not actually need, this does not mean that people will acquire items if their purchase has significant risk tied to them. Using time series information across 35 years, the empirical analyses show that people are less likely to think buying a home is a good idea due to change in the level of equity market volatility brought about by infectious diseases. Even though panic buying occurs during epidemics and pandemics, this is not an indication that decision-making about purchases is wholly irrational. In uncertain times when infectious disease outbreaks make equity markets unpredictable, people rationally seek to minimize the level of personal losses they experience as much as possible.